2018
DOI: 10.1186/s12864-018-4887-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis of Enterococcus faecalis: insights into their environmental adaptations

Abstract: BackgroundEnterococcus faecalis is widely studied as a common gut commensal and a nosocomial pathogen. In fact, Enterococcus faecalis is ubiquitous in nature, and it has been isolated from various niches, including the gastrointestinal tract, faeces, blood, urine, water, and fermented foods (such as dairy products). In order to elucidate the role of habitat in shaping the genome of Enterococcus faecalis, we performed a comparative genomic analysis of 78 strains of various origins.ResultsAlthough no correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 48 publications
3
43
0
Order By: Relevance
“…In general, no obvious differences arose from the profiles and sequences of virulence genes between strains obtained from foodstuffs/livestock and those causing human infections and only the occurrence of cyl and cpsC-K seemed lineage (ST)-specific (Table S5). These data support previous works indicating the generalist lifestyle of E. faecalis and the opportunist nature of the human infections they cause [31,51].…”
Section: Virulence Gene Profilessupporting
confidence: 91%
See 1 more Smart Citation
“…In general, no obvious differences arose from the profiles and sequences of virulence genes between strains obtained from foodstuffs/livestock and those causing human infections and only the occurrence of cyl and cpsC-K seemed lineage (ST)-specific (Table S5). These data support previous works indicating the generalist lifestyle of E. faecalis and the opportunist nature of the human infections they cause [31,51].…”
Section: Virulence Gene Profilessupporting
confidence: 91%
“…Intact or relics of prophages highly identical to sequences from common enterococcal prophages such as phiL1A and vB_IME197 were identified in most strains, but the exact phage(s) present in each genome cannot be ruled out with accuracy. The phiL1A and vB_IME197 phages are widespread in E. faecalis from variable sources [31] and were originally described in clinical settings in UK and China, respectively [54,55] [58]. In this study, this phage was putatively identified in three related ST476 strains from hospitalized patients, farm and retail chicken in China and Tunisia (Table S6), once more enphasizing the lack of a demarcation between clinical and non-clinical genomes in relevant mobile genetic elements (MGEs).…”
Section: Prophagesmentioning
confidence: 85%
“…Based on SNP analysis, we observed an overall diverse population of optrA -positive E. faecalis (range 0-17.712 SNPs) with a correspondence between the sequence types identified (17 STs, 18 branches) (Figure 1, Table S1 in the Supplemental material). Strains originating from the same source or country were dispersed across the different tree branches, suggesting no significant correlation between strain origin and phylogeny as commonly observed in E. faecalis [31]. These results further confirm the easy promiscuity of optrA that has been identified in enterococci from highly variable epidemiological and genetic backgrounds [2, 32].…”
Section: Resultssupporting
confidence: 70%
“…All of them are classified as temperate Siphoviridae bacteriophages originally obtained from variable sources (humans, farms, hospital sewage) [4850]. The phiEf11 and LP-101 phages are not present in V583 in contrast to phiFL1A and vB_EfaS_IME197, which corresponded to the predominant prophages in the collection analysed and are also widespread in E. faecalis from variable sources [31]. Both phiFL1A and IME197 were originally described in clinical settings in UK and China, respectively [49, 51].…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest alternating periods of genetic isolation and gene flow in different hosts for some E. faecalis lineages from wild birds. A reassessment of the population structure of the species through increased sampling of nonhuman isolates is therefore necessary to further identify host‐specific populations suggested here and elsewhere (He et al ., ). The presence and diversity of pheromone‐responsive plasmids in most birds, as well as in human isolates, confirms the relevance of this plasmid family in the biology of E. faecalis as a species.…”
Section: Discussionmentioning
confidence: 97%